Desenvolvimento de um sistema de monitoramento de corrente elétrica para o estudo da usinabilidade do aço UNS S32760 - Augusto Freitas Vieira Campidelli (2020)
In the last decades, the use of stainless steels in several engineering fields have increased considerably. Among these alloys, superduplex stainless steels are characterized by their high content of alloying elements and biphasic microstructure composed of similar amounts of austenite and ferrite. These attributes award the superduplex steels with high corrosion resistance and mechanical strength, as well as good ductility. Consequently, the machinability of these steels is considered difficult, which results in significant production costs. Therefore, the investigation of superduplex steels behavior during machining operations is of utmost importance for the development of measures that contribute to an increase in productivity. In the light of these facts, the aim of this work is to study the influence of cutting parameters on the machinability of UNS S32760 superduplex stainless steel. For this purpose, 39 turning tests were performed using different values of cutting speed and feed rate. During the tests, the values of the cutting force components, main spindle current consumption and chip temperature were monitored. For the monitoring and acquisition of the electric current values, a measurement system, composed of a Hall Effect sensor connected to a microcontroller, was developed. The proposed system presented superior performance when compared to a commercial system, being able to monitor the main cutting force indirectly through the values of the main spindle current with a coefficient of determination of 0.92. The results revealed that the feed rate have a greater influence on the cutting force components. The cutting speed influence, on the other hand, proved to be dependent on the feed rate employed, becoming more evident for feed rate values above 0.15 mm/rev. The main spindle current behavior during the turning operation was similar to that observed for the main cutting force, which evidences the correlation between these variables. Regarding the temperature measurement, the cutting speed increase resulted in higher chip temperatures, especially for conditions where high feed rate values were used. Moreover, it was noticed that the chip thickening caused by the feed rate increase led to the measurement of lower temperature values by infrared radiation.